ANALISIS PENGARUH INTERKONEKSI DISTRIBUTED GENERATION (PLTSA SUWUNG) TERHADAP RUGI-RUGI DAYA DAN KEANDALAN PADA PENYULANG SERANGAN - Nusaman, I Made Gusmara; Sukerayasa, i Wayan; Hartati, Rukmi Sari (Jurnal Teknologi Elektro; Vol 14 No 2 (2015): (July - December) Majalah Ilmiah Teknologi Elektro, 2015)
The distributed generation technology or in this case abbreviated DG is a kind of power plants with small scale which prioritizes the utilization of renewable energy resources such as wind, water, solar, geothermal, ocean waves (Wave Energy), ocean currents (Ocean Current Energy), biomass, and biogass to produce the electrical energy with range of power generation between 1 kW-10 MW. One of the DG in Bali and still in operation is the garbage power plant which located in Suwung, South Denpasar. An analysis has been done using load flow analysis and reliability assessment to determine the effect of DG interconnection against the power losses and the level of reliability on the Serangan feeder. Based on the research that has been done, DG intercon-nection on the Serangan feeder decrease the power losses and increase the reliability and it can visible from the acquisition of SAIFI and SAIDI index which decreased. The best location of DG interconnection to get low of the power losses and the high level of reliability is at 97% from the total length of the feeder. At that location the power losses is decrease as big as 4.5 kW or 11.25% of the total power lossess without the DG interconnection and decrease of the SAIFI and SAIDI index respectively to 0.1 failure/customers/year and 1.4150 hour/ customer/year
Keywords: Kata Kunci: Rugi-Rugi Daya, Keandalan, Load Flow , Analysis, Reliability Assessment